2022
DOI: 10.3390/batteries8050046
|View full text |Cite
|
Sign up to set email alerts
|

Calendering of Silicon-Containing Electrodes and Their Influence on the Mechanical and Electrochemical Properties

Abstract: The process chain of electrode production includes calendering as a crucial process step to enhance the volumetric energy density as well as to influence the particle-pore-structure and simultaneously the mechanical and electrochemical properties of the electrode coating. A further way to improve the volumetric energy density is the usage of other materials with higher specific capacity, such as silicon instead of graphite as the active material for anodes. In this study, both opportunities, calendering and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Due to the aforementioned more elastic deformation behavior of the HC particles compared with the Gr particles, higher line loads are apparent for the Gr/HC blend anodes. Consequently, the formation of new particle bonds with the current collector at higher calendering forces is impeded, which was also recently shown for silicon/Gr composites by Scheffler et al [ 32 ]…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Due to the aforementioned more elastic deformation behavior of the HC particles compared with the Gr particles, higher line loads are apparent for the Gr/HC blend anodes. Consequently, the formation of new particle bonds with the current collector at higher calendering forces is impeded, which was also recently shown for silicon/Gr composites by Scheffler et al [ 32 ]…”
Section: Resultsmentioning
confidence: 63%
“…Due to the aforementioned more elastic deformation behavior of the HC particles compared with the Gr particles, higher line loads are apparent for the Gr/HC blend anodes. Consequently, the formation of new particle bonds with the current collector at higher calendering forces is impeded, which was also recently shown for silicon/Gr composites by Scheffler et al [32] Moreover, it can be observed that blending Gr and HC leads to an overall increase in adhesive strength compared with the pure material of Gr. This can be explained by the distribution of the HC in the blend.…”
Section: Mechanical and Electrical Propertiesmentioning
confidence: 53%
“…A calendering study with multiple compression levels is conducted in ref. [25] considering silicon-containing composites in electrodes. It shows that the silicon content directly affects the electrode deformation after calendering.…”
Section: Doi: 101002/ente202200893mentioning
confidence: 99%
“…Since it has been shown in various studies that calendering can significantly influence the microstructure of electrodes, the anodes were not calendered. [14][15][16]…”
Section: Coating and Dryingmentioning
confidence: 99%
“…The decrease of mechanical properties occurs due to the breakage of particle-binder interactions, since the increase of mechanical properties can be traced back to increasing particle-particle interlockings. [14,15] In contrast, electrodes with a too dense microstructure, due to high calendering, can lead pore blockage for electrolyte wetting, and this increase of density can ultimately lead to limitations of lithium diffusion. [14,41,42] In the context of high calendering of electrodes, improved mechanical properties through particle-particle interlocking cannot be guaranteed, and too high calendering should be avoided.…”
Section: Cmc-d Cmc-s Cmc-a A-m150 A-m155mentioning
confidence: 99%